Evaluation of the nutrition and function of cow and goat milk based on intestinal microbiota by metagenomic analysis. Issue 4 (26th March 2018) - Wang, Zhaoxia; Jiang, Shuaiming; Ma, Chenchen; Huo, Dongxue; Peng, Qiannan; Shao, Yuyu; Zhang, Jiachao
Abstract : A high-throughput 16S rRNA sequencing technology was applied to study changes of the intestinal microbiota in mice after the administration of cow and goat milk. We show a correlation between the gut microbiota and the nutrients in milk. Abstract : Milk contains nutrients needed by the body, and the main components of different animal milk vary. Accordingly, we evaluated cow and goat milk's nutrition and their effects on the gut microbiota in mice models using a high-throughput 16S rRNA sequencing technology. The intestinal microbiota of mice changed significantly after the intake of cow and goat milk, and the goat milk had a greater effect on the intestinal microbial community than the cow milk. Bifidobacterium, Allobaculum, Olsenella and Akkermansia grew significantly in both cow and goat milk groups compared with the control group, indicating that milk positively affected their growth. We also found that the citrate cycle (TCA cycle), pyruvate metabolism, and amino sugar and nucleotide sugar metabolism, as well as lipoic acid metabolism, were higher in the goat milk group than in the cow milk group. Association analysis of milk components and their representative intestinal microbiota showed that casein, αs1 -casein, and β + κ-casein were positively correlated with Enterococcus and Allobaculum, and negatively correlated with Roseburia . Protein and αs2 -casein were positively associated with Akkermansia, Bifidobacterium and Eubacterium .